2013
DOI: 10.1007/978-3-642-39371-6_32
|View full text |Cite
|
Sign up to set email alerts
|

Looking Back at Facebook Content and the Positive Impact Upon Wellbeing: Exploring Reminiscing as a Tool for Self Soothing

Abstract: The premise of this paper is to explore the potential of reminiscing in facilitating self soothing. The research presented looks at people"s activities on Facebook and whether these particular activities impact upon their perceived sense of wellbeing, furthermore, whether specific Facebook activities enable a self -soothing effect when feeling low in mood. A survey was distributed amongst Facebook users. The results from the study appear to indicate that in comparison to other Facebook activities, looking back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Viewing one's SNS content may be beneficial for other reasons. For example, looking at old content depicting past positive events may promote adaptive effects from positive reminiscing (Good et al, 2013). Likewise, feedback on SNSs tends to be highly positive (Valkenburg et al, 2006;Rideout et al, 2018;Wenninger et al, 2019).…”
Section: Browsing One's Own Profilementioning
confidence: 99%
“…Viewing one's SNS content may be beneficial for other reasons. For example, looking at old content depicting past positive events may promote adaptive effects from positive reminiscing (Good et al, 2013). Likewise, feedback on SNSs tends to be highly positive (Valkenburg et al, 2006;Rideout et al, 2018;Wenninger et al, 2019).…”
Section: Browsing One's Own Profilementioning
confidence: 99%
“…Another study found that passively using one's own Facebook profile page can have a positive impact on emotional well-being, as scrolling through old posts and pictures had a self-soothing effect on respondents (Good, Sambhantham, & Panjganj, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Web is increasingly providing access to the provision of health care via the Web and plays a significant role in providing information on mental health. This includes a variety of resources that facilitate support and self-help, such as information sites; social networking sites; communities as well as others (Good et al, 2013; Van de belt et al, 2010). When we consider that in 2010, people in the USA spent 10 billion dollars on self-help materials (Harwood & L'Abate, 2010); it is hardly surprising that a significant number of people are increasingly also looking to the Web for self-help resources.…”
Section: Using the Web As A Resource For Self-help In Mental Healthmentioning
confidence: 99%